CSBA Executive Director Cites Future Importance of Bombers - Cortes, Lorenzo (Defense Daily, 2003)
"The Air Force doesn't have a bomber program until sometime in the 2030s,"Andrew Krepinevich, told HASC. "Yet in Allied Force [Kosovo], bombers flew one percent of the sorties and dropped 11 percent of the PGMs (precision-guided munitions). In Afghanistan, they flew 20 percent of the sorties and dropped 70 percent of the PGMs. In the recent war, they flew 3 percent of the sorties and dropped 28 percent of the PGMs. Bombers count." In testimony to the HASC earlier in the year, [James Roche] described a force that included the potential for 150 FB-22s, along with 60 B- 1B equipped with Lockheed Martin Joint Air-to-Surface Standoff Missiles, 21 B-2s and 381 F/A-22s with the Small Diameter Bomb (SDB) (Defense Daily, Feb. 28). The Air Force also wants to make a major buy of Lockheed Martin's F-35 Joint Strike Fighter (JSF) as well.